Association of Frailty Index at 66 Years of Age with Health Care Costs and Utilization Over 10 Years in Korea: Retrospective Cohort Study - Jieun Jang; Anna Kim; Mingee Choi; Ellen P McCarthy; Brianne Olivieri-Mui; Chan Mi Park; Jae-Hyun Kim; Jaeyong Shin; Dae Hyun Kim (JMIR Public Health and Surveillance)
Abstract BackgroundThe long-term economic impact of frailty measured at the beginning of elderhood is unknown. ObjectiveThe objective of our study was to examine the association between an individual’s frailty index at 66 years of age and their health care costs and utilization over 10 years. MethodsThis retrospective cohort study included 215,887 Koreans who participated in the National Screening Program for Transitional Ages at 66 years of age between 2007‐2009. Frailty was categorized using a 39-item deficit accumulation frailty index: robust (<0.15), prefrail (0.15‐0.24), and frail (≥0.25). The primary outcome was total health care cost, while the secondary outcomes were inpatient and outpatient health care costs, inpatient days, and number of outpatient visits. Generalized estimating equations with a gamma distribution and identity link function were used to investigate the association between the frailty index and health care costs and utilization until December 31, 2019. ResultsThe study population included 53.3% (n=115,113) women, 32.9% (n=71,082) with prefrailty, and 9.7% (n=21,010) with frailty. The frailty level at 66 years of age was associated with higher cumulative total costs (robust to frail: $19,815 to $28.281; PPPPPPPPPPPPPP ConclusionsOur study demonstrates the potential utility of assessing frailty at 66 years of age in identifying older adults who are more likely to incur high health care costs and utilize health care services over the subsequent 10 years. The long-term high health care costs and utilization associated with frailty and prefrailty warrants public health strategies to prevent and manage frailty in aging populations.